Adat Court in Indonesia’s Judiciary System: A Socio-Legal Inquiry - Herlambang P. Wiratraman (Journal of Asian Social Science Research, 2022)
This article addresses the question of how the constitution drafters considered the existence of a plural legal system in Indonesia, especially the adat judicial system. There are several sociological arguments for constitutional pluralism, empirical and normative claims, and the necessity of formalizing adat court. Constitutional pluralism identifies the phenomenon of a plurality of constitutional sources and claims of final authority which create a context for potential constitutional conflicts that are not hierarchically regulated. Hence, this article argues that ‘constitutionalizing’ does not mean ‘formalization’, or even ‘structuring the adat court under the state formal judicial system’. This should be critically assessed not merely on recognition, but also on protection, especially to exercise fundamental values of social significance. It considers the concepts of ‘self-recognition based adat court’ and ‘regional recognition based adat court’ as important in defending universal values to respect and protect the rights of the people, including their traditional systems. By doing so, this article aims to contribute to the studies on the importance of the plural legal system in plural societies like Indonesia.